Administrative and Legal Support Challenges of Environmental Safety Under Globalization - Haraschuk, Volodymyr; Zelinska, Yana; Spasenko, Viktoriia; Shynkaruk, Oleksandra (European Journal of Sustainable Development, 2020)
The article investigates the underlying challenges of administrative and legal support of environmental safety under globalization. The current globalization conditions and factors affecting the transition of environmental safety from local to a global level, which is due to globalization processes in the world and a number of global anthropogenic challenges, are analyzed. The emphasis is focused on the impact of globalization on the adoption of international treaties in the field of environmental safety. The importance of administrative and legal environmental safety at the state level for the implementation of the executed international treaties is substantiated. The obsolescence and underperformance of the current state of administrative and legal support of environmental safety in Ukraine is grounded, the necessity for its optimization is proved, the weaknesses are highlighted and the need for introducing a number of improvement directions, including propaganda of a careful attitude to the environment, is substantiated; regulatory support for the effective distribution of functions and viable mechanism for management of central and local executive authorities, local government institutions on the formation and implementation of state policy components in the field of climate change in accordance with their competence; regulatory actions of joint events and cooperation of domestic government bodies in the area of environmental safety with similar bodies of neighboring countries; implementation ensuring of the provisions of the Association Agreement between Ukraine and the European Union, the European Atomic Energy Community and their member states related to climate change; ensuring the fulfillment of Ukraine’s obligations regarding reporting on international agreements in the field of climate change, etc. Keywords: globalization, environmental safety, state environmental policy, legal support of environmental safety, administrative and legal support for environmental safety of Ukraine, international legal support for environmental safety